2014
DOI: 10.1038/ejcn.2014.243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mediterranean-style diet on glycemic control, weight loss and cardiovascular risk factors among type 2 diabetes individuals: a meta-analysis

Abstract: The present meta-analysis provides evidence that MSD improves outcomes of glycemic control, body weight and cardiovascular risk factors in T2D patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
150
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(177 citation statements)
references
References 53 publications
12
150
1
14
Order By: Relevance
“…48 In the Pre vención con Di eta Med iterránea (PREDIMED) trial, participants assigned a MedSD had a 30% reduction in major CV events compared with the low-fat control group. 50 Subsequent analyses of PREDIMED have supported previous observational studies 51,52 and randomized controlled trials and have concluded that the MedSD promotes metabolic improvement in DM and MetS. 53 Similar results were seen in a meta-analysis of 50 studies representing 523,906 subjects.…”
Section: Healthy Behaviour Managementsupporting
confidence: 56%
“…48 In the Pre vención con Di eta Med iterránea (PREDIMED) trial, participants assigned a MedSD had a 30% reduction in major CV events compared with the low-fat control group. 50 Subsequent analyses of PREDIMED have supported previous observational studies 51,52 and randomized controlled trials and have concluded that the MedSD promotes metabolic improvement in DM and MetS. 53 Similar results were seen in a meta-analysis of 50 studies representing 523,906 subjects.…”
Section: Healthy Behaviour Managementsupporting
confidence: 56%
“…Of interest is a 2015 meta-analysisof MEP eating patterns (15). The meta-analysis included nine studies with 1,178 people with diabetes (five of these studies are included in Table 1; the other four were <12 weeks or not specific to diabetes).…”
Section: Benefits Of the Mep In Diabetes Managementmentioning
confidence: 99%
“…1, 2 Comprehensive meta-analyses showed significant inverse associations between high adherence to Mediterranean diet and risk of type 2 diabetes (T2D), 3 and improvements in glycemic control among T2D patients following a Mediterranean diet compared with a low-fat diet. 4 …”
Section: Introductionmentioning
confidence: 99%